Response lags and environmental dynamics of restoration efforts for Lake Rotorua, New Zealand. (July 2015) - Mueller, Hannah; Hamilton, David P; Doole, Graeme J
Abstract Regulatory responses to degradation of freshwater ecosystems have been characterized by long response times and have often failed to prevent declining health or to implement successful restoration programs. We studied environmental and management dynamics of ecosystem restoration in Lake Rotorua, New Zealand, where land use intensification is the main driver of water quality decline. Water quality decline, invasions by exotic submerged plants and occurrences of algal blooms have led to a number of in-lake interventions such as herbicide spraying (to control submerged plants) and dosing of inflows with Alum to flocculate phosphorus (and reduce algal blooms). Management of land use to reduce nutrient run-off has also been initiated. Based on the drivers-pressures-state-impact-response (DPSIR) framework, water quality changes and management responses were examined by studying research publications and data from 1922 to 2013. Multinomial regression analysis based on the generalized maximum entropy model was used to investigate the five categories of DPSIR and examine relationships of environmental dynamics and regulatory responses. We tested whether the visibility of ecosystem degradation in the public sphere, and social lag times to respond to them, were drivers of failures of these regulatory responses. Our study shows that management was reactive, and regulations often took effect only when ecosystem decline was already well advanced. There was a disconnect between land use intensification and its role in driving water quality change. Our results indicate that science can better inform management decision making by providing a holistic framework integrating ecological knowledge, economic interest and societal constraints.